2018
DOI: 10.1016/j.jacr.2018.09.032
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria® Shoulder Pain-Atraumatic

Abstract: Shoulder pain is one of the most common reasons for musculoskeletal-related physician visits. Imaging plays an important role in identifying the specific cause of atraumatic shoulder pain. This review is divided into two parts. The first part provides a general discussion of various imaging modalities (radiographs, arthrography, nuclear medicine, ultrasound, CT, and MRI) and their usefulness in evaluating atraumatic shoulder pain. The second part focuses on the most appropriate imaging algorithms for specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 96 publications
(115 reference statements)
1
26
1
Order By: Relevance
“…No MRI nding was correlated with CMS, in agreement with Park et al 32 , who showed a correlation of CMS with total arthrography score but not with MRI ndings. Unlike Anh et al 25, we did not nd any correlation between MRI ndings and pain, but we did not rate IGHL enhancement.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No MRI nding was correlated with CMS, in agreement with Park et al 32 , who showed a correlation of CMS with total arthrography score but not with MRI ndings. Unlike Anh et al 25, we did not nd any correlation between MRI ndings and pain, but we did not rate IGHL enhancement.…”
Section: Discussionsupporting
confidence: 89%
“…As the estimation of pain duration provided by patients may be imprecise, a pain score system with time intervals was used to limit this potential bias. Since the correlation between MRI ndings and the range of motion each direction is still debated 24,32,35 , only global motion scores were considered. There was no control group, and no systematic clinical or MRI follow-up of the patients included.…”
Section: Discussionmentioning
confidence: 99%
“…RCT pathology can be due to tears, inflammation, and degeneration. Although imaging modalities like radiographs, ultrasound, and computed tomography (CT) have indications for evaluating the shoulder, MRI is the gold standard according to the American College of Radiology (ACR) appropriateness criteria for assessing both traumatic and atraumatic shoulder pain in suspected rotator cuff disease [ 15 , 16 ]. While radiographs provide an important initial study and ultrasound may be helpful in detecting full-thickness tears for evaluating the shoulder, MRI provides excellent, comprehensive imaging of soft-tissue structures, specifically the rotator cuff and labrum, and is thus the exam of choice.…”
Section: Rotator Cuff and Musclesmentioning
confidence: 99%
“…Additionally, attrition of the rotator cuff is thought to contribute to glenohumeral joint imbalance, superior migration of the humeral head, and narrowing of the subacromial space [ 38 , 39 ]. Although radiographs and ultrasound can be helpful in evaluating shoulder impingement, MRI gives detailed information about the extra-articular findings that can be a cause or result of shoulder impingement [ 16 ]. Acromial morphology can predispose to impingement.…”
Section: Rotator Cuff and Musclesmentioning
confidence: 99%
See 1 more Smart Citation